Mesh-shelters provide more effective long-term protection than tube-shelters or mulching for restoration of Pinus halepensis in a Mediterranean arid ecosystem - Oliet, Juan A.; Planelles, Rosa; Artero, Francisco; Jacobs, Douglass F. (Frontiers in Forests and Global Change, 2023)
Forest restoration is challenging in arid and semiarid lands. Research has identified ecotechnologies that may alleviate stressful conditions of planted seedlings, but studies are often limited to the first few years of regeneration establishment. Over 20 years, we tested the effects of tree shelters (mesh- and tube-shelters) and competition suppression (two types of synthetic mulch and manual weeding) on soil water content and development of Pinus halepensis on an arid site in southeastern Spain. Competition suppression increased soil water content at shallow depths only using a polyethylene sheet, with no effect on survival. Tree shelters had a much greater effect than competition suppression on tree responses. Survival was mostly affected by shelter type, with lower survival in tube-shelters compared to mesh-shelters and non-protected seedlings; differences began after the first year, but became more pronounced following an intense drought at three years. Survival for pines protected by mesh-shelters was significantly higher than for non-protected seedlings beginning at six years, and mortality did not stabilize until 15 years. After 20 years, survival ranked in order of mesh-shelters (57.5%), non-sheltered (46%), and tube-shelters (29.5%). Effects of shelter type on growth response over time followed an opposite pattern, with differences declining when pines outgrew the height of the shelter after three years. Competition suppression had no effect on pine growth. Thus, 20 years after planting, tube-shelters and competition suppression treatments were relatively ineffective at improving survival or growth of Pinus halepensis. Mesh-shelters are recommended as the most effective protection method for restoration under arid site conditions.